1-[5-(4-Methoxyphenyl)-3-phenyl-4,5-dihydro-1H-pyrazol-1-yl]ethanone - Abbas, A.; Hussain, S.; Hafeez, N.; Lo, K.M.; Hasan, A. (International Union of Crystallography, 2010)
The title molecule, C18H18N2O2, is V-shaped with the pyrazoline moiety being inclined to the adjacent phenyl ring by an angle of 6.49 (9)degrees, while the 4-methoxy-substituted ring is inclined to the pyrazoline ring by 82.99 (9)degrees. In the crystal, adjacent molecules are linked by C-H center dot center dot center dot O interactions, forming chains propagating in [100]. There are also C-H center dot center dot center dot pi interactions involving adjacent molecules and those related by an inversion center.